Study of drug resistance in isolates from ICU infections in a tertiary care hospital - Kombade, S.; Agrawal, G. (Scientific Journal of Medical Science, 2014)
Background, Nosocomial Infections are an important cause of morbidity, mortality and economic problems especially in intensive care units (ICUs). Aim, This study was conducted to estimate the clinical and bacteriological profile and their antibiotic sensitivity testing in ICU infected patient.Materials and methods, 245 patients clinically diagnosed to have infections in ICU were studied prospectively in the Department of Microbiology, Indira Gandhi Govt. Medical College from Sep. 2009- Dec. 2011. Depending on sites of infections various samples were collected and processed as per the standard guidelines. The isolates were subjected to antimicrobial susceptibility testing by Kirby Bauer disc diffusion method as per CLSI 2012 guideline. Results, The incidence of pneumonia, blood stream infection and urinary tract infections was 61.6%, 20.1% and 11% respectively. P. aeruginosa (16.3%) was the commonest isolate in ICU infection followed by A. baumannii (13.5%) and K. pneumoniae (11.8%) with maximum sensitivity to imipenem, piperacillin tazobactum and amikacin. All Staphylococcus and Enterococcus species were sensitive to vancomycin and linezolid. Gram-negative pathogens acquired from ICU patients in our settings show high resistance to antibiotics. Conclusion, Regular monitoring of the pattern of resistance of common pathogens in the ICUs is critical in planning the best routines for empirical treatment of infectious patients.